An Assessment of Information Audit with Special Reference to Medical Library, University of Colombo - Ravikumar, M.N.; Jayasundara, C.C. (My University, 2010)
Libraries need to adopt new methods to manage the large quantity of available literature in an effective manner. The paper describes an information audit conducted at Medical Library of University of Colombo using Henczels’ (2001) seven stage information audit model. Sample of the study consisted user groups of the Medical Library. Self- administrated questionnaires and in-house statistics were used as research instruments to collect the data. The study received the response rate of 69.07%. After the assessment of information audit in Medical Library of University of Colombo, It is recommended that the library should focus on the enhancements of collections and equipments to cater the new demands especially on electronic media. Conducting user education programmes using new technology; adding latest reference books; subscribing more e-journals and databases; increasing internet facilities; providing access to eresources to users from their own desktops; enhancing resource sharing activities; training programmes for staff and strengthening the online information delivery services in library networks were suggested for future library improvements.